Pengaruh Disiplin Kerja dan Budaya Organisasi terhadap Kinerja Karyawan pada PT.Ambar Borneo di Sangatta Utara - Illiyyin Apriliani Putri (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
The influence of work discipline and organizational culture of employee performance at PT.Ambar Borneo or Ambar Borneo company, North Sangatta. This study uses a quantitative descriptive method. The purpose of this study is to test how the influence of work discipline and organizational culture on employee performance at PT.Ambar Borneo in North Sangatta. The population in this study amounted to 40 respondents from employees of PT.Ambar Borneo in North Sangatta on Jl.Poros Kabo, Kel. Swarga Bara, Kec.Sangatta Utara, Kabupaten Kutai Timur. The independent variables in this study are work discipline and organizational culture, and the dependent variable in this study is performance. The results of data analysis are processed with SPSS version 26. Data collection techniques are based on primary data from observations, interviews, questionnaires, and documentation.This study uses data analysis techniques for validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and dominant tests. The results of the study that the variables of work discipline and organizational culture simultaneously have a significant effect on performance.